Pelibatan Audiens Generasi Milenial Pada Program “Netizen Bertanya Ustad Menjawab”Di Televisi Muhammadiyah - Nabila Putri Falaqiah; Makroen Sanjaya (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
Audiences are the main consideration in the production of a TV program, and play a major role in determining the script that will be made. The "Netizen Bertanya Ustad Menjawab" program involves the audience to participate by sending questions in the form of videos which will later be aired during the broadcast. The purpose of this research is to find out the involvement of millennial generation audiences in the "Netizen Bertanya Ustad Menjawab" program and also want to know the stages of production implementation in the "Netizen Bertanya Ustad Menjawab" program. This research uses audience theory, using a qualitative approach, and descriptive methods. Data collection techniques were carried out through observation, documentation, and in-depth interviews. The results of this study indicate that the program "Netizen Bertanya Ustad Menjawab" can be a place to interact with the audience or TVMu viewers so that the audience knows more about religion from the perspective of Muhammadiyah and adjusted by Tarjih Muhammadiyah. The production process of the Netizen Bertanya Ustad Menjawab event program is carried out by tapping or recording, which means it is not broadcast live. By involving the millennial generation audience in the event program, it can be an attraction in itself for the event program because it shows a video of the audience while giving questions submitted to the ustad who is broadcasting at that time.